2000
DOI: 10.1093/ajcn/71.3.674
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of fermented and nonfermented dairy products: effects on cholesterol concentrations and metabolism

Abstract: The objective of this article was to review existing literature concerning the effects and mechanisms of action of fermented dairy products on serum cholesterol concentrations. Although not without exception, existing evidence from animal and human studies suggests a moderate cholesterol-lowering action of fermented dairy products. Mechanistically, fermented milk has been shown to cause an increase in human gut bacterial content. These bacteria, once resident in the large intestine, are believed to ferment foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
146
1
11

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(166 citation statements)
references
References 30 publications
8
146
1
11
Order By: Relevance
“…The cholic and deoxycholic bile acids are produced from cholesterol by hepatocytes and are conjugated with glycine and taurine, respectively. These acids enter the small intestine, where they are absorbed and directed to liver, and a decrease in bile acid recycling would ultimately result in a lowering of serum cholesterol concentration because cholesterol is used for bile acid synthesis (St-Onge et al 2000). However, we did not measure the amount of bile acid synthesis to support this speculation.…”
Section: Resultsmentioning
confidence: 92%
“…The cholic and deoxycholic bile acids are produced from cholesterol by hepatocytes and are conjugated with glycine and taurine, respectively. These acids enter the small intestine, where they are absorbed and directed to liver, and a decrease in bile acid recycling would ultimately result in a lowering of serum cholesterol concentration because cholesterol is used for bile acid synthesis (St-Onge et al 2000). However, we did not measure the amount of bile acid synthesis to support this speculation.…”
Section: Resultsmentioning
confidence: 92%
“…In vitro simulation has suggested that whereas some species of L. and B. lose viability during gastric transit, ingestion with milk proteins improves their tolerance to the pH of upper GI system (Charteris, 1998). In addition to its potential effect on bacterial viability, milk has been hypothesized to contain components such as 3-hydroxymethyl glutarate and orotic acid that may independently lower cholesterol (Mann, 1977;St-Onge et al, 2000). Although changes in intestinal microflora were not assessed in the present study, fecal bacteria and enzymes were altered by provision of L. acidophilus DDS-1 and B. longum UABL-14 in a concurrently conducted study in postmenopausal women (Greany et al, 2004) suggesting that the bacteria did remain viable and reach the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…in n-3 PUFA-depleted mice (58). Moreover, it has been shown that an increase in lactic acid bacteria, such as Bifidobacterium spp., is related to a reduction in cholesterol absorption (154) and an increase in bile acid deconjugation, which leads to more excretion of bile acids and elimination of hepatic cholesterol (155).…”
Section: Introductionmentioning
confidence: 99%